High Throughput Screening Method for Identifying Potential Agonists and Antagonists of Arabidopsis thaliana Cytokinin Receptor CRE1/AHK4 - Klimeš, Pavel; Turek, Dušan; Mazura, Pavel; Gallová, Lucia; Spíchal, Lukáš; Brzobohatý, Břetislav (Frontiers in Plant Science, 2017)
The CRE1/AHK4 cytokinin receptor is an important component of plants’ hormone signaling systems, and compounds that can alter its activity have potential utility for studying the receptor’s functions and/or developing new plant growth regulators. A high-throughput method was developed for screening compounds with agonist or antagonist properties towards the CRE1/AHK4 cytokinin receptor in a single experiment using the Nanodrop II liquid handling system and 384-well plates. Potential ligands are screened directly, using a reporter system in which receptor signaling activity triggers expression of b-galactosidase in Escherichia coli. This enzyme generates a fluorescent product from a non-fluorescent substrate, allowing the agonistic/antagonistic behavior of tested compounds to be assayed in relation to that of an internal standard (here the natural ligand, trans-zeatin). The method includes a robust control procedure to determine false positive or false negative effects of the tested compounds arising from their fluorescent or fluorescent-quenching properties. The presented method enables robust, automated screening of large libraries of compounds for ability to activate or inhibit the Arabidopsis thaliana cytokinin receptor CRE1/AHK4.